(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Durjoy Datta had a place with a generation of remarkable Indian writers who burst into limelight and continued to blaze all through the twenties. The Boy with a Broken Heart is a romantic book by Durjoy Datta. Durjoy Datta’s books and composing style is incorporated on the mindset of youth and their snapshots of happy just as troubles in their relations. Datta’s books on which this examination is led and paper is composed, are genuinely exceptionally contacting and it portrays how one can experience tops in life at a second and needs to confront valleys the other. A start to finish examination of the fiction of Durjoy Datta’s uncovers that the soul of family relationship shapes its methodology, headway and merry culmination. The obvious piece of Durjoy Datta’s inventive work is the feasible perspective embedded in each novel. As he is known for his clearness, the message is continually exceptionally clear. The insightful truth that the events pass on has its beginning stage in human mindset.